Design low carbon campus landscapes at Premier Polytechnic Sultan Salahuddin Abdul Aziz Shah, Shah Alam, Selangor / Nurmunira Razmi - Razmi, Nurmunira (2017)
Campus physical development plan is an effective tool to shaping campuses life, especially among students to promote a sustainable living community. Aim of this research is to enhancing the quality of campus outdoor environment by applying low carbon @ green landscapes and sustainable development. Premier Polytechnic Sultan Salahuddin Abdul Aziz Shah (PSA) was selected because of respond to the government planning to make a green campus for polytechnic to increase the capacity of TVET and Education for Sustainable Development (ESD) in the Commonwealth countries. As stakeholders in TVET, polytechnic institutions that are directly involved in supporting and implementing initiatives that TVET-ESD also in line with the aspirations of the country. The approach taken for its implementation is to make students as a key technology and green practices at polytechnic. Green program run will start with initiatives without cost, easy, can involve many participants and its impact can be calculated and reported in terms of financial savings and carbon footprint reduction. With the design approaches and strategies that can solved the issues and problems to achieve a better environment towards green and sustainable campus.